An Ecological Study of Identity in Teaching English as a Foreign Language in Light of the Dynamic Systems Model of Role Identity - Wang, Rouhua; Elahi Shirvan, Majid; Taherian, Tahereh (Frontiers in Psychology, 2021)
Influenced by the growing urge of investigating the combined nature of teacher identity with the dynamic teacher professional learning processes in recent years (Garner & Kaplan, 2018), the present study aimed to cast an ecological look at identity role construction and change in L2 teaching. To this aim, Kaplan and Garner’s (2017-18) Dynamic Systems Model of Role Identity (DSMRI) meta-theoretical framework was employed with the centrality of social–cultural roles in framing an EFL teacher’s experiences and guiding actions. In a single-case study, a Chinese EFL teacher’s dynamic construction of identity (as a single-case design) was traced in three phases: before a practicum (teacher professional development program), during the practicum, and during the first year of teaching. A triangulation of data was used to ensure the adequacy and representativeness of the required data to be next analyzed qualitatively to find traces of change and development in the teacher’s ontological beliefs, goals, self-perceptions, and action possibilities. The DSMRI-oriented analysis of pre-, mid-, and post-practicum data emphasized the traces of role identities of the teacher trainee in her professional development process, that also created both emerging patterns and emerging challenges in her role identity that fostered a more negotiated, adaptive and realistic teacher role identity. This study substantiated the usefulness of the DSMRI for viewing language teachers’ professional development and the dynamic identity development processes as several temporal and situated factors contribute to the alignment or misalignment of a teacher’s ontological beliefs, goals, self-perceptions, and action possibilities.